Tuesday

July 22, 2014

July 22, 2014

Posted by **kathy** on Monday, January 23, 2012 at 8:50pm.

- college algebra -
**Steve**, Tuesday, January 24, 2012 at 12:33am2/3 x^2 - x - 3 = 0

2x^2 - 3x - 6 = 0

x = [3 ± √57]/4

**Related Questions**

Algebra - For this equation x^(2) + x + 2 which you can't factor but then you ...

Algebra - Use the quadratic formula to find the real solutions: 2x/x-3 + 2/x = 3...

Algebra II - 1)What method(s) would you choose to solve the equation: x2 + 2x - ...

Algebra - Consider the equation: 4x^2 – 16x + 25 = 0 (a) Show how to compute the...

Algebra - Consider the equation 4x^2 – 16x + 25 = 0. (a) Show how to compute the...

Math - Find the real solutions, if any, to this equation. Use the quadratic ...

algebra - Solve the quadratic equation: 2x(squared)+6x+12=0 I know you have to ...

math - find the real solutions using the quadratic formula 6-(1/x)-(4/x^2)=0

Math - I am given 4 choices for the problem the square root of 8x -2 = the ...

Algebra - Compute the value of the discriminant and give the number of real ...